Simulating fracture network permeability in brown-coal slopes - Hu, R.; Walsh, S.D.C.; Missen, J.; Anderson, N. (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Slope stability of open cut brown-coal mines depends upon the permeability of the fracture network within the coal seam. In this paper, we provide a detailed analysis of the role of the fracture distribution on the permeability of brown-coal slopes and outline a model to capture this behaviour. Brown coal is relatively impermeable, but heavily fractured. Hence, a stress-dependent fracture permeability model is employed that considers the spacing, orientation, aperture and frequency of the fractures to produce an effective permeability. We discuss how this model captures fracture heterogeneity and the effect of changing stress conditions on the fluid flow. Fracture data collected from real mines exhibit significant degrees of heterogeneity, in particular, they may include a wide range of apertures and inter-fracture separations. The results of the effective permeability model demonstrate that in many cases slope permeability is dominated by highly permeable but low probability fractures. These results emphasise the need for models capable of capturing the effects of heterogeneity and uncertainty on the slope behaviour.